Environmental planning for business competitiveness - Carranza N., Raymundo (2002)
The general conception of entrepreneurs is that strict environmental regulation, would result in the migration of entrepreneurs to countries where regulations are more flexible without affecting the productive capacity of enterprises; but according to recent research, companies with strict environmental regulations are more competitive by having plants with more efficient modern equipment and processes in the transformation of inputs, allowing optimization of costs, and minimizing waste.